1999
DOI: 10.1097/00005053-199901000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Abuse and Neglect as Risk Factors for Suicidal Behavior in Adolescent Inpatients

Abstract: The aim of this study was to assess relative risk of histories of different types of abuse (sexual, physical, and emotional) and neglect (physical and emotional) for suicidal behavior (attempts, ideation, and self-mutilation) in psychiatrically hospitalized adolescents. Seventy-one adolescent inpatients (34 boys, 37 girls) completed self-report measures of abuse and neglect, current suicidal ideation, and lifetime suicide and self-mutilation attempts. The prevalence of sexual and physical abuse was 37.5% and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
87
2
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(101 citation statements)
references
References 33 publications
9
87
2
3
Order By: Relevance
“…Our results indicate that both sexual abuse and physical neglect are associated with NSSI, which is consistent with some prior research on this relation (Joiner et al, 2007;Lipschitz et al, 1999;Simpson & Porter, 1992). This investigation is the first to our knowledge to also document a strong relation between childhood emotional abuse and NSSI.…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicate that both sexual abuse and physical neglect are associated with NSSI, which is consistent with some prior research on this relation (Joiner et al, 2007;Lipschitz et al, 1999;Simpson & Porter, 1992). This investigation is the first to our knowledge to also document a strong relation between childhood emotional abuse and NSSI.…”
Section: Discussionsupporting
confidence: 92%
“…Again, correlations with promiscuity, runaway, or suicidal attempts were described elsewhere (e.g., Bartoi & Kinder, 1998;Hartman, Burgess, & McCormack, 1987;Kelly et al, 1992;Lipschitz, Winegar, Nicolaou, Hartnick, Wolfson, & Southwick, 1999;Stiffman, 1989). Significant associations of nonpsychotic distress symptoms (i.e., anxiety, depression, somatization, and dissociation) with abuse also replicate previous reports (Bryer, Nelson, Miller, & Krol, 1987;Goff, Brotman, Kindlon, Waites, & Amico, 1991;.…”
Section: Discussionsupporting
confidence: 80%
“…Lipschitz and colleagues [39], who conducted a cross-sectional study on 71 adolescent inpatients, found that emotional neglect was a significant predictor of both suicide attempts and self-mutilation. They also reported that emotional neglect was more strongly associated with suicidal ideation and self-mutilation than physical abuse or physical neglect.…”
Section: Studies On the Association Between Maltreatment And Suicidalmentioning
confidence: 99%